Barriers and Enablers in Implementing SDGs Through Community Empowerment Programs - Abidin, Zaenal; Azman, Azlinda; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2025)
This article discusses the effectiveness of the implementation of community empowerment programs managed by Lazismu East Java in supporting the achievement of the Sustainable Development Goals (SDGs) through the management of zakat, infaq, shadaqa, and partnership (ZISKA). With a qualitative case study approach, this study identifies internal and external factors that affect Lazismu's performance, including human resources, institutional networks, stakeholder support, and applicable regulations. Although Lazismu has enormous potential in fund management and organizational networks, the implementation of empowerment programs still tends to be pseudo-community empowerment, namely empowerment that is symbolic and has not touched the root of the community's structural problems. Additional issues encompass insufficient resources, inadequate monitoring and evaluation of initiatives, and suboptimal management of socio-economic and technological impacts. This report recommends that Indonesia implement internal reforms, enhance institutional capacity, and employ macrosocial workers to develop more effective, sustainable, and structurally oriented empowerment models that facilitate inclusive growth.